The Effect of the MTHFR C677T Mutation on Athletic Performance and the Homocysteine Level of Soccer Players and Sedentary Individuals - YÜCEL, HAYRİYE SELDA (DE GRUYTER POLAND SP ZOO, 2016)
This study investigated athletic performance and homocysteine (Hcy) levels in relation to the methylenetetrahydrofolate reductase (MTHFR) C677T mutation and explored the relationship between this mutation and other cardiac risk factors in soccer players and sedentary individuals. The study groups consisted of randomly selected soccer players (n= 48) from the Turkish Super and Major League and sedentary male students (n= 48) aged 18-27. Anthropometric variables, aerobic and anaerobic thresholds were measured, furthermore, biochemical assays were performed. The level of HDL cholesterol, LDL cholesterol, triglyceride, Hcy, folate, vitamin B12, hemogram and MTHFR C677T was investigated. The results showed that there was a statistical difference between the two groups in terms of body mass, body fat, the BMI, the aerobic threshold heart rate (ATHR), aerobic threshold velocity (ATVL) and anaerobic threshold velocity (ANTVL). The soccer players were found to have lower levels of triglyceride, total cholesterol and LDL cholesterol, and higher levels of folate than the sedentary participants. The analysis of the alleles of the MTHFR C677T polymorphism showed that the participants that carried TT genotypes had a lower level of vitamin B12 and folate, and a higher level of Hcy than the participants carrying CC and CT genotypes. In conclusion, the baseline homocysteine and cardiovascular fitness levels of healthy young males with the TT genotypes of the MTHFR C677T genotype were found to strongly correlate with their levels of Hcy.
Keywords: MTHFR C677T; soccer; homocysteine; athletic performance; METHYLENETETRAHYDROFOLATE REDUCTASE GENOTYPE; CARDIOVASCULAR-DISEASE; PHYSICAL-ACTIVITY; RISK-FACTORS; LIFE-STYLE; EXERCISE; POLYMORPHISM; ASSOCIATION; SUPPLEMENTATION; ADOLESCENTS